2009
DOI: 10.1073/pnas.0904285106
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally separable Shh domains in the midbrain define distinct dopaminergic progenitor pools

Abstract: Midbrain dopamine neurons (mDA) are important regulators of diverse physiological functions, including movement, attention, and reward behaviors. Accordingly, aberrant function of dopamine neurons underlies a wide spectrum of disorders, such as Parkinson's disease (PD), dystonia, and schizophrenia. The distinct functions of the dopamine system are carried out by neuroanatomically discrete subgroups of dopamine neurons, which differ in gene expression, axonal projections, and susceptibility in PD. The developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
122
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 41 publications
15
122
2
1
Order By: Relevance
“…Consistent with the literature and our previous observations Echelard et al, 1993;Nouri et al, 2015;Puelles and Rubenstein, 2015), βgal + /Foxa2 + cells are observed in the midbrain, and well rostral to the ZLI, in the diencephalon (Fig. 1A-B′ At midbrain levels, Shh/Foxa2 derivatives have been previously described, and include DA and RN populations (Blaess et al, 2011;Hayes et al, 2011;Joksimovic et al, 2009). To identify mdFP derivatives rostral to the midbrain, we examined coronal sections through the rostral midbrain/caudal diencephalon.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Consistent with the literature and our previous observations Echelard et al, 1993;Nouri et al, 2015;Puelles and Rubenstein, 2015), βgal + /Foxa2 + cells are observed in the midbrain, and well rostral to the ZLI, in the diencephalon (Fig. 1A-B′ At midbrain levels, Shh/Foxa2 derivatives have been previously described, and include DA and RN populations (Blaess et al, 2011;Hayes et al, 2011;Joksimovic et al, 2009). To identify mdFP derivatives rostral to the midbrain, we examined coronal sections through the rostral midbrain/caudal diencephalon.…”
Section: Resultssupporting
confidence: 63%
“…In the early embryo, differentiating Th + DA neurons are observed in the midbrain with a caudal limit at the MHB. The anterior limit of this Th + DA cohort is approximately near the base of the zona limitans intrathalamica (ZLI), the boundary between presumptive developmental segmental units, prosomeres 2 and 3 (p2 and p3) (Joksimovic et al, 2009;Nouri et al, 2015;Puelles and Rubenstein, 2015). Because these neurons appear to be generated from the midbrain as well as presumptive p1, p2 and p3, some have called these mesodiencephalic DA neurons (Puelles and Rubenstein, 2015;Veenvliet and Smidt, 2014), as opposed to midbrain DA neurons (Arenas et al, 2015;Blaess and Ang, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we show that MbDA neuron progenitors are poised to respond to SHH, FGF8 and WNT1 signaling. Previous studies have shown that canonical DEVELOPMENT WNT signaling can antagonize Shh expression (Joksimovic et al, 2009). However, our early deletion of Wnt1 shows that Shh expression is not increased and suggests that WNT1 does not drive…”
Section: Discussioncontrasting
confidence: 38%
“…Of particular interest are the Mb dopamine (MbDA) neurons because they modulate brain function and are centrally involved in schizophrenia, addiction and Parkinson's disease. During embryogenesis, MbDA neurons are derived from multiple lineages originating within the mesencephalon (mes), which is the Mb primordium (Zervas et al, 2004;Joksimovic et al, 2009;Brown et al, 2011;Hayes et al, 2011;Blaess et al, 2011). The molecular identity of the mes is based on a combinatorial code of transcription factors and is patterned by signaling molecules, including WNT1 (reviewed by Zervas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%